Uma proposta de intervenção pedagógica no ensino de matemática contextualizada na astronomia - Silva, Welberton Rios da (2023)
The present work, having the perception that Mathematics teaching is still offered in an abstract way and distant from the students' reality, leads us to the guiding question: “how to make Mathematics classes more attractive, giving them a new meaning through contextualization in Astronomy?” In response to this question, this intervention research seeks to take a historical approach to the use of Mathematics related to the evolution of discoveries and observations of planets in the Solar System, correlating with mathematical content generally seen in an abstract way in High School. This research targets 154 students from the 1st to 3rd year of high school in a public school, and 30 students from the undergraduate course in Mathematics at UEFS, who were subjected to practical activities in the form of workshops and mini-courses. , which involved information and communication technology (ICT) tools, modeling and prototyping of experiments contextualized in Astronomy. The project, based on pedagogical interventions, involved carrying out 05 workshops covering the contents of functions and geometry, for high school students, while for Mathematics degree students, 02 short courses: one showing the historical importance of Mathematics in the discovery of the planets Neptune and the dwarf planet Pluto; the other mini-course presented practical activities relating Astronomy and Mathematics. As a result of the workshops and short courses, the incorporation of a broader vocabulary within an interdisciplinary context stands out, along with the development of experimental support apparatus, mathematical and astronomical simulations, which were condensed in the form of the educational product of this research, entitled “Activity Proposals for Teaching Contextualized Mathematics in Astronomy”.